A sustainable method for effective regulation of anaerobic granular sludge: Artificially increasing the concentration of signal molecules by cultivating a secreting strain. (November 2015) - Ding, Yangcheng; Feng, Huajun; Huang, Wenkun; Shen, Dongsheng; Wang, Meizhen
Graphical abstract: Highlights: QS from signal molecule secreting strains regulates anaerobic sludge granulation. AI-2 QS regulation accelerates sludge aggregation. Aggregation yields increased extracellular polymeric substance (EPS) production. Granulation promotion by C4-HSL regulation was less than by AI-2. The negative effect of DSF-QS restrained granular diameter growth, EPS production. Abstract: This study introduces sustainable quorum sensing (QS) granulation for anaerobic granular sludge (AnGS) and investigates the efficiency of three types of signal molecules on regulating AnGS granulation. The signal molecules of a secreting strain cultured in a QS regulating reactor increased their concentrations in an expanded granular sludge bed reactor throughout the granulating process. Increasing content of autoinducer-2 (AI-2) strengthened interspecific QS communication and gave a best performance with larger granular diameters, higher extracellular polymeric substance (EPS) production and relative hydrophobicity (RH). N -butyryl-homoserine lactone (C4-HSL) QS regulation was also favorable for granular growth, but its regulation was less than that of AI-2-QS. The AnGS granulated under these two types of QS regulations guided more filamentous bacteria to take part in granulation. Under diffusible signal factor (DSF)-QS regulation, the sludge had a lower granular level with a smaller granule diameter, lower EPS production (RH) when compared that of control medium.